Staying on track through a pandemic: A report on measures taken to reduce risk of COVID in Formula 1. A team doctors perspective - McFarquhar, A. (BASEM, 2020)
Covid-19 has proven difficult to contain with numbers still rising in many places in the world. With the global pandemic set to continue into the winter, the question of how we keep a covid-free environment in Formula 1 is crucial in order to protect people`s health and livelihoods, and those of their colleagues too.